The Long Journey of Extracellular Vesicles towards Global Scientific Acclamation - Marco Pirisinu (Tabriz University of Medical Sciences, 2023)
Extracellular vesicles (EVs) are a heterogeneous class of cell-derived vesicles that are responsible for eliciting a wide array of biological processes. After decades of intense investigation, the therapeutic potential of EVs will be finally explored in a series of upcoming clinical trials. EVs are rapidly changing the understanding of human physiology and will undoubtedly transform the field of medicine. The applicability of EVs as diagnostic biomarkers and treatment vectors has captured the attention of the scientific community and investors, facilitating the rapid progression of numerous EVs-based platforms. This mini-review provides an outline of the pioneering discoveries, and their respective significances, on progressing EVs toward clinical use. We focus the attention of the readers on several promising classes of EVs that hold major opportunities to translate in clinical practice. Market analysis and future challenges facing EVs-based therapies are also discussed.